FAKTOR KETERLAMBATAN PENCARIAN PENGOBATAN PASIEN TUBERKULOSIS PARU DI KABUPATEN BANYUMAS - Madyo Maryoto; Suci Khasanah (Viva Medika, 2016)
ow Case Detection Rate (CDR) could be interpreted that there are many cases of pulmonary tuberculosis that has not been detected and given the treatment, so it can be a source ofinfection for people in the neighborhood, so it needs an increase in efforts to find active case(MOH, 2011) , Delays in treatment lead to the transmission, as well as the impact the increasedrisk of disease transmission. So search delays pulmonary TB treatment resulted in increasednumbers of cases of pulmonary TB. Objectives of this study was to analyze the delay of treatment seeking behaviorof Pulmonaru TB patients in Banyumas Regency. The study design using analytic descriptivestudy. Samples in this study were patients who had intensive phase of TB treatment (first 2 months)in Primary Helath care center of Banyumas regency. The sample size of this study were 102respondents, purposive sampling technique was used in this study. In which the variables includes:age, sex, occupation, family income, education, marital status, knowledge, perception and delayseeking treatment of TB patients. Analysis of this study was use simple logistic regression andlinear regression. The result of this study shows that the majority of pulmonary TB patients were not delayin seeking of treatment. It was about 56 respondents (54.9%). There is influence between age,occupation, family income, education level, knowledge, perception and the delay treatmentseeking behavior of pulmonary TB patients in Banyumas Regency. There are no influencesbetween gender, marital status and the delay treatment seeking behavior of pulmonarytuberculosis patients in Banyumas Regency. Keywords: Age, Sex, Occupation, Family Income, Education Level, Marital Status, Knowledge,Perception, The Delay Treatment Seeking Behavior,TB